Alzheimer’s disease: current status of genetics research - Guerreiro, Rita J. (Henry Stewart Talks, 2014)
Main features of Alzheimer's disease (AD) including: Epidemiology, Clinic/diagnosis, Neuropathology, Genetics, Familial vs. Sporadic forms, Molecular mechanisms, Genome-wide association & Next-generation sequencing studies in AD